Measurement report: A survey of meteorological and cloud properties during ACTIVATE’s postfrontal flights and their suitability for Lagrangian case studies - F. Tornow; F. Tornow; A. Fridlind; G. Tselioudis; B. Cairns; A. Ackerman; S. Chellappan; S. Chellappan; D. Painemal; D. Painemal; P. Zuidema; C. Voigt; et al. (Atmospheric Chemistry and Physics)
Postfrontal clouds, often appearing as marine cold-air outbreaks (MCAOs) along eastern seaboards, undergo overcast-to-broken cloud regime transitions. Earth system models exhibit diverse radiative biases connected to postfrontal clouds, rendering these marine boundary layer (MBL) clouds a major source of uncertainty in projected global-mean temperature. The recent NASA multi-year campaign Aerosol Cloud meTeorology Interactions oVer the western ATlantic Experiment (ACTIVATE) therefore dedicated most of its resources to sampling postfrontal MCAOs, deploying 71 flights from 2020 through 2022. We provide an overview of (1) the synoptic context within the parent extratropical cyclone, (2) the meteorological conditions with respect to the season, (3) the suitability of case data and measurements for Lagrangian analysis and modeling studies, and (4) the encountered cloud properties. A proposed subset of flights deemed most suitable for Lagrangian modeling case studies is highlighted throughout. Such flights typically cover a greater fetch range, were better aligned with the MBL wind direction, and revisited sampled air masses when key instruments were operational. Like many other flights, these flights often probed cloud formation and some cloud regime transitions. Surveying cloud properties from remote sensing and in situ probes, we find a great range in cloud-top heights and a relatively large concentration of frozen hydrometeors, which suggest strong free tropospheric entrainment and secondary ice formation, respectively. Both processes are expected to leave marked signatures in cloud evolution, such as strongly ranging cloud droplet number concentrations. ACTIVATE data combined with satellite retrievals can establish observational constraints for future model improvement work.